Averting a school crisis: a risk management guide on preparedness for school faculty and parents - Santiago, Cody M. (Rowman & Littlefield, 2018)
Understanding how to prepare -- School politics -- The incident command system and why you should care -- The meat & potatoes of the plan -- Use what you have -- Emergency scenarios to consider -- Special events at your school -- School transportation -- Crisis management -- Testing your plans -- The prepared school you hope to be